A theory-based analysis of the implementation of online asynchronous telemedicine platforms into primary care practices using Normalisation Process Theory - Cara Leighton; Natalie Joseph-Williams; Annavittoria Porter; Adrian Edwards; Alison Cooper (BMC Primary Care)
Abstract Background Online asynchronous telemedicine platforms are effective and have been implemented in primary care practices, but it is unclear whether implementation was successful. Implementation has not been studied on a large scale in primary care practice. Normalisation Process Theory is a sociological theory used to understand how complex practices can be embedded into routine practice. We aimed to identify and evaluate factors affecting, and make recommendations for, implementation of online asynchronous telemedicine platforms in primary care practice using Normalisation Process Theory. Methods A systematic search was carried out across four databases. Studies included were empirical research, published between January 2015 and November 2022, of qualitative, quantitative and mixed methods designs, focusing on implementation of online asynchronous telemedicine platforms designed for two-way secure communication between patients and healthcare professionals to give or receive medical advice in primary care. Data extraction was guided by the domains of Normalisation Process Theory: context, mechanisms, outcomes. Results 25 reports from 21 primary studies were obtained. COVID-19 changed the context in which asynchronous platforms were implemented into primary care, due to restrictions on face-to-face contact. Coherence is supported by online platforms providing benefits for patients. Healthcare staff felt confident using platforms and better teamworking added to cognitive participation, however patient ‘misuse’ of platforms hindered this. Collective action was negatively affected by poor usability and integration of platforms into practice systems. Reflexive action through large- and small-scale studies had allowed improvements to be made, but poor response rates inhibit this. Outcomes include changed roles and responsibilities for staff and patients and high patient satisfaction. There are concerns regarding confidentiality and health inequities. Conclusions Increased workload, lack of integration into existing systems and poor usability affect implementation. Widespread implementation of online platforms in primary care practices can be supported by policy-makers through consistent guidelines to improve platforms’ content, functionality and compatibility with clinical systems to try to enable improvements in practice. Further research should explore patient groups or needs for which online platforms are most suitable, reasons why online platforms work better for different patients and how different patient groups can be supported to benefit from asynchronous telemedicine.